Systemic Approach to Solve Problem of Managing Zakat in Contemporary Muslim Society in Indonesia - Hardiyanto, Nugroho; Choirul Afif, Nur; Bayu Aji Sumantri, Muhammad; Haizam Mohd Saudi, Mohd (International Journal of Engineering and Technology, 2018)
In a Muslim society, the issue of zakat has always been an interesting topic to be discussed. It is related to the fact that zakat from Muslim society has a huge potential. In Indonesia for instance, using the assumption of 1.7% of Indonesia GDP it reached 270 trillion Rupiah. This number is highly significant even though the management of zakat conducted by government agency from local until national level is yet to be optimized. This research is discussing several factors that causing failure in zakat management using the systemic approach. This approach is trying to analyze several factors of failures in optimizing zakat collection in Indonesia and alternative solution for the problem.Â Â